2010
DOI: 10.1002/adma.200904264
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Stress Transfer in a Graphene Monolayer Nanocomposite

Abstract: Graphene is one of the stiffest known materials, with a Young's modulus of 1 TPa, making it an ideal candidate for use as a reinforcement in high-performance composites. However, being a one-atom thick crystalline material, graphene poses several fundamental questions: (1) can decades of research on carbon-based composites be applied to such an ultimately-thin crystalline material? (2) is continuum mechanics used traditionally with composites still valid at the atomic level? (3) how does the matrix interact wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
555
6
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(612 citation statements)
references
References 31 publications
46
555
6
5
Order By: Relevance
“…However, no apparent shifts are detected when UTG is present. On the contrary, the characteristic G-band, clearly visible in all the composite spectra, is up-shifted up to 12 cm -1 with increasing UTG content, suggesting interactions between TPU and UTG due to interfacial stress transfer [30].…”
Section: More Sensitive Information On What Concerns Possible Interacmentioning
confidence: 90%
“…However, no apparent shifts are detected when UTG is present. On the contrary, the characteristic G-band, clearly visible in all the composite spectra, is up-shifted up to 12 cm -1 with increasing UTG content, suggesting interactions between TPU and UTG due to interfacial stress transfer [30].…”
Section: More Sensitive Information On What Concerns Possible Interacmentioning
confidence: 90%
“…[16] Young et al have shown (for graphene-PMMA composites at least), that this poor performance is due to very poor stress-transfer at the interface. [17] This is different to polymer-nanotube composites where good stress transfer has been observed by many researchers. [18,19] In principle, stress transfer can be improved by functionalisation.…”
Section: Introductionmentioning
confidence: 99%
“…maximum shear stress of 2.3 MPa at the edge of the sheet; graphene-matrix interfacial shear stress is on the order of 0.25-0.8 MPa and with a maximum value of 1 MPa [42]; fracture stress of a graphene sheet is larger than 100 GPa and the failure strain loading is on the order of 20% [28]. …”
Section: Materials Propertiesmentioning
confidence: 99%
“…Novoselov, Young and their colleagues at the University Manchester [42][43][44] studied the change in the strain distribution on graphene, and observed that the strain across the flake is uniform at the applied strain up to 0.6%. After that cracks form in polymer coating layers, with the graphene remaining intact.…”
Section: Properties Of Graphene/polymer Interface: Inverse Modelingmentioning
confidence: 99%